Odpowiedź:
[tex]\frac{3}{4} - \frac{1}{8} = \frac{6}{8} - \frac{1}{8} = \frac{5}{8}[/tex]
[tex]\frac{1}{2} - \frac{1}{6} = \frac{3}{6} - \frac{1}{6} = \frac{2}{6} = \frac{1}{6}[/tex]
[tex]\frac{5}{6} - \frac{1}{3} = \frac{5}{6} - \frac{2}{6} = \frac{3}{6} = \frac{1}{2}[/tex]
[tex]\frac{5}{6} - \frac{1}{8} = \frac{20}{24}- \frac{3}{24} = \frac{17}{24}[/tex]
[tex]\frac{3}{4} - \frac{3}{10} = \frac{15}{20} - \frac{6}{20} = \frac{9}{20}[/tex]
[tex]\frac{1}{4} - \frac{1}{15} = \frac{15}{60} - \frac{4}{60} = \frac{11}{60}[/tex]
Szczegółowe wyjaśnienie:
Mam nadzieję że pomogłam :)